The geology of carbonaceous deposits (Carboniferous) of the South Urals (Fedorovskaya sequence, Sukharysh syncline) - A.V. Snachev (Учёные записки Казанского университета: Серия Естественные науки)
The geological structure of coal formations of the Sukharysh syncline, which is located in the Kopeysk-Bredy subzone of the Alapaevsk-Adamovka structural-formational zone, was studied. The focus was specifically on the deposits of the Fedorovskaya sequence (C2fd) with outcrops in the sections along the Uvelka River and in few roadside pits. The width of the sequence is about 1000 m. The Middle Carboniferous (Bashkirian) age of the deposits was reliably dated based on the fossil faunal finds. It was shown that shales and aleurolites, which are widespread in the limestones of the Fedorovskaya sequence, belong to the low-carbon type and fall into the field of the siliceous-carbonate unit. The carbonaceous matter is developed in the form of scattered impurities, concentrated in the ultrafine veinlets and laminas, and corresponds to higher kerites subjected to catagenesis and the early stage of green shales facies. The organic carbon content is up to 20%, and, thus, the rock appears to be opaque. Sedimentation process took place in the isolated local shallow-water depressions under the geodynamic conditions of collision. The terrigenous material was formed as a result of the destruction of the underlying rocks of the major and average element composition of the Berezinskaya sequence. The maturity of the deposits consistently increases from the Tugundinskaya to Fedorovskaya sequences.